2010
DOI: 10.1200/jco.2009.26.1685
|View full text |Cite
|
Sign up to set email alerts
|

Surgery With or Without Preoperative Paclitaxel and Carboplatin in Early-Stage Non–Small-Cell Lung Cancer: Southwest Oncology Group Trial S9900, an Intergroup, Randomized, Phase III Trial

Abstract: A B S T R A C T PurposePatients with early-stage non-small-cell lung cancer (NSCLC) have a poor prognosis even after complete resection. Earlier studies of preoperative (induction) chemotherapy in resectable NSCLC demonstrated feasibility and encouraging survival data. This randomized phase III trial compared overall survival (OS) for preoperative paclitaxel and carboplatin followed by surgery with surgery alone in patients with early-stage NSCLC. Patients and MethodsPatients with clinical stage IB-IIIA NSCLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
158
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(182 citation statements)
references
References 26 publications
18
158
2
4
Order By: Relevance
“…The first approach is advocated by Albain et al (2009) who showed that lobectomy will add little to Chemo-radiotherapy for patients with stage IIIa (N2) non-small-cell lung cancer, at the expense of higher mortality (evidence level 1b) [20]. The second approach is supported by the S9900 trial follow up published in 2010 which continues to show that the best treatment for N2 resectable lung cancer would be induction chemotherapy followed by surgery (evidence level 1b) [21]. Rocco et al (2010) is supportive of the third approach, concluding that standard treatment of initially resectable stage IIIa NSCLC remains surgery followed by adjuvant chemotherapy (evidence level 2a) [22].…”
Section: Preoperative V Postoperative Stagingsupporting
confidence: 48%
“…The first approach is advocated by Albain et al (2009) who showed that lobectomy will add little to Chemo-radiotherapy for patients with stage IIIa (N2) non-small-cell lung cancer, at the expense of higher mortality (evidence level 1b) [20]. The second approach is supported by the S9900 trial follow up published in 2010 which continues to show that the best treatment for N2 resectable lung cancer would be induction chemotherapy followed by surgery (evidence level 1b) [21]. Rocco et al (2010) is supportive of the third approach, concluding that standard treatment of initially resectable stage IIIa NSCLC remains surgery followed by adjuvant chemotherapy (evidence level 2a) [22].…”
Section: Preoperative V Postoperative Stagingsupporting
confidence: 48%
“…The controversy arises in operable early cancer in the presence of a histologically proven single station mediastinal node (cT1-3, N2). The current best practice evidence supported by the S9900 trial follow up published in 2010 continues to show that the best treatment for N2 resectable lung cancer would be induction chemotherapy followed by surgery (evidence level 1b) [19]. Multizonal lung cancer is thought to be a systemic disease beyond cure by surgery alone, and is best treated by chemo-radiotherapy.…”
Section: Indicationsmentioning
confidence: 99%
“…Przedoperacyjna (indukcyjna) chemioterapia była przedmiotem kilku badań III fazy, których wyniki były rozbieżne [27][28][29][30][31][32]. W większości badań obserwowano względnie wysoki odsetek obiektywnych odpowiedzi, a w kilku -także wydłużenie czasu przeżycia wolnego od nawrotu lub czasu całkowitego przeżycia.…”
Section: Przedoperacyjna Chemioterapiaunclassified